Life Skills Training On Self Esteem, Emotional Intelligence And Mental Wellbeing Among Children Residing At Selected Institutionalized Homes, Puducherry: A Pilot Study. - E, Varun Babu; Abirami, M. (Journal of Neonatal Surgery, 2025)
The research examines the effects of life skills training on self-esteem, emotional intelligence, and mental well-being in children living in chosen institutional homes. Aim: The study aims to assess the impact of life skill training on self-esteem, emotional intelligence and mental wellbeing among children residing at selected institutionalized home, Puducherry. Methods: The study sample comprises 16 children residing at selected institutionalized home, Puducherry. A Purposive sampling technique was used to select the sample who fulfilled the criteria. Rosenberg’s self-esteem scale was used to measure the self-esteem of children. Schutte Emotional Intelligence Scale (SEIS) was used in the study to assess the emotional intelligence of the children. Modified Warwick Edinburgh Mental wellbeing Scale was used in the study to assess the mental wellbeing of the children. Results: The data reveals that the pre-test scores of children, 43.8% had low and 56.2 % had normal level of self esteem. Comparatively Post-test scores of children showed there was increased in the level of self esteem with 87.5% had normal level and 12.5% had high level of self esteem. The pre-test scores of emotional intelligence was 18.7% had low, 75% had moderate and 6.3 % had high level of emotional intelligence. Comparatively Post-test scores of children showed slight increase in the level of emotional intelligence with 81.3% had moderate and 18.7% had high level of emotional intelligence. The Pre-test scores of mental wellbeing was 12.5% had inadequate, 75% had moderately adequate and 12.5 % had adequate level of mental well-being. Comparatively Post-test scores of children showed slight increase in the level of mental well-being with 56.2% had moderately adequate and 43.8% had adequate level of mental well-being. Conclusion: The study concluded that there was a positive correlation between Emotional Intelligence and mental well-being among institutionalized children. The study result shows that there was a significant difference in pre and post level of self esteem, Emotional Intelligence and mental well-being of the children after receiving life skill training.